TOKOH ULAMA HADIS DI MALAYSIA - Muhammad Fajri Yusuf (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
Kassim Ahmad is a multi-talented intellectual. He is known as a poet, cultural expert and reliable politician. Kassim''s interest in politics and philosophy introduced him to the La Rouche political-philosophical movement in the United States. The anti-hadith movement in Malaysia emerged in the 1980s which was spearheaded by Kassim Ahmad. The thoughts of Inkar Sunnah Kassim Ahmad can be seen in his book